Seminar of Zakat Literation for Introduction Types of Zakat: Implementation in Puri Asri Housing Communities, Jetis District, Bantul Regency - Izza, M.Yusril Hafidz Nur; Ramadhan, Fathurrohman; Dewi, Afifah Itsnaeni; Soraya, Aisya Nailis; Yunitasari, Bella; Lusiani, Fidya; Mahendra, Maulana Rizka; Hsb, Putri Annisa; Prastiwi, Putri; Salma, Syarifah; Purwati, Wahyu Sri (Journal of Islamic Economy and Community Engagement, 2020)
AbstractCommunity service regarding zakat is aimed at educating and developing community literacy through youth community, Puri Asri Street, Tri Mulyo, Jetis, Bantul. Zakat, which is the fourth pillar of Islam, has a mandatory legal status according to shari'ah. The majority of Muslim communities in Indonesia have not yet paid zakat correctly. Most only know zakat fitrah only and others who have known other types of zakat have not performed zakat correctly. So, it is very necessary for a socialization activity to add insight into the scientific community in tithe. The participants in the socialization program consisted of 20 young people, with different levels of education. Ranging from junior high school level to college students. From the questionnaire data distributed to participants (pre-test) 80,7% did not understand zakat well, so this socialization was needed. After the socialization was held a post-test was held to find out the increase in knowledge and scientific uptake of the participants, and it was stated that 91,6% had understood the material of the zakat presented.Keywords: Zakat, Socialization, Education